1993
DOI: 10.1017/s1352465800010493
|View full text |Cite
|
Sign up to set email alerts
|

Cue-Controlled Relaxation and “Aromatherapy” in the Treatment of Speech Anxiety

Abstract: The purpose of this investigation was to examine the separate and combined effects of cue-controlled relaxation training and "aromatherapy" as treatments for reducing speech anxiety. Thirty-six speech anxious subjects were randomly assigned to one of four conditions: cuecontrolled relaxation with a word cue, cue-controlled relaxation with an aroma cue, "aromatherapy" alone, and a wait list (i.e., control) group. Prior to treatment, subjects completed the Personal Report of Confidence as a Speaker, Fear of Nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…One RCT of aromatherapy in men with speech anxiety found no difference in the anxiety reduction of men treated with aromatherapy and men in a control group. 80 A systematic review of RCTs of aromatherapy delivered through massage found that the intervention resulted in significantly lower anxiety levels than a control intervention in hospitalised cancer, cardiac and intensive care patients. 81 However, participants were not specifically selected for anxiety, the reduction in anxiety was reported to be transient, and the trials contained methodological flaws.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One RCT of aromatherapy in men with speech anxiety found no difference in the anxiety reduction of men treated with aromatherapy and men in a control group. 80 A systematic review of RCTs of aromatherapy delivered through massage found that the intervention resulted in significantly lower anxiety levels than a control intervention in hospitalised cancer, cardiac and intensive care patients. 81 However, participants were not specifically selected for anxiety, the reduction in anxiety was reported to be transient, and the trials contained methodological flaws.…”
Section: Resultsmentioning
confidence: 99%
“… 195 ‐ 202 Rational emotive therapy has been found to be more effective, 197 but relaxation has been found to be superior to aromatherapy. 200 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spector, Carey, Jorgensen, Meisler, and Carnrike (1993) found little reduction in speech anxiety following jasmine or spiced apple aromatherapy. Spector, et al noted that participants exposed to the scents showed little expectation that this type of treatment would effectively reduce their speech anxiety so the authors suggested that researchers consider participants' beliefs.…”
mentioning
confidence: 91%
“…Steel and Tisserand (cited in Vukovic, 1995), both aromatherapists, found that calming oils such as neroli, jasmine, and lavender produce more alpha and theta brain waves, indicative of relaxation and well-being. In another study, speech anxiety was found to decrease more in the experimental group than in the control group following the use of AT (Spector et al, 1993).…”
Section: Massagementioning
confidence: 91%